SYNTHESIS, STRUCTURE, AND PHYSICAL PROPERTIES OF METHYLAMMONIUM LEAD IODIDE SINGLE CRYSTAL - Raissa
The hybrid perovskites of methylammonium lead triiodide (CH3NH3PbI3) hold great promise as active layer for solar cells. Solar cell efficiencies which is higher than ~18% has been achieved using this material as a light absorber. This hybrid perosvkite has unique physical properties such as high extinction coefficients, large optical absorption, excellent thermal stability, and large intrinsic dipole moments. However, many questions remain about the nature of the fundamental optical excitation processes. More comprehensive understanding on their interaction with light will allow us to find out the fundamental limits of their intrinsic properties as solar cell material. Therefore, the study of the photophysical investigations on single crystals will allow to access the intrinsic properties. We will report about the synthesis of methylammonium iodide (MAI), which together with lead (II) iodide (1:1) give rise to the hybrid perovskite CH3NH3PbI3. Single crystals of size of about 0.225 x 0.225 x 0.05 mm3 were grown by drop casting of the CH3NH3PbI3 solution in ????- butyrolactone on glass substrates. The crystals appear to have good quality and xray spectrogram did not show the presence of different material phases. Therefore, we measured both steady state and time-resolved photoluminescence (PL) of the CH3NH3PbI3 single crystals at different temperatures (5 K-300 K). The emission peak at room temperature is about 780 nm. When the sample is cooled down to 150 K, interestingly, the emissions show two peaks at 760 nm and 780 nm. This double feature persists down to 30 K, where only one emission peak is observed (~780 nm). The observation of the change of the PL spectra is accompanied by a well-known phase transition (from orthorhombic to tetragonal phase). X-ray diffraction experiments are performed to analyze the details of the phase transition, in particular below 30 K and the position of the organic ligands in the structure. Photoluminescence experiments performed at different power intensity show a peculiar blue shift with the increase of excitation power. The time resolved fluorescence show an increase of the decay time with decreasing temperature from 82.7 ns (293 K) to 5367 ns (50 K), with a small decrease to 5043 ns at 5 K. This data is explained in terms of the band structure of the hybrid perovskite.